Externalities and allocation criteria in Tort Law. Pricing strategy v. sanctioning strategy: First part - Saavedra Velazco, Renzo (2014)
With the arrival of the Economic Analysis of Law, some scholars began to consider Law as a set of “official prices” given by the legislature or the courts. Such change of perspective created some ius-economic inconsistencies because  a  large segment of the doctrine didn’t realize the impossibility of efficiently regulating the economy by recurring only toorders and mandates.In this article, the author argues that it is necessary to establish the ius-economic differences between sanctions and prices, i.e. between those hypotheses in which Lawsets a price on a behavior and those cases which Law looks forward to impose a sanction. Such ideas should be applied to Tort Law, specifically in the definition and understanding of allocation criteria.